Developing a Sustainability Evaluation Framework for Higher Education Institutions: A Case Study Integrating Sustainable Development Goals in Pakistan - Aimen Iftikhar Ahmed; Hasnain Shahzad; Faryal Wajid Khan; Rubab Ahmed; Ar. (Dr.) Adnan Anwar (Social Science Review Archives, 2025)
By their education, research, and institutional practices, Higher Education Institutions (HEIs) contribute significantly to sustainable development. Though many HEIs in the world have centers and programs for sustainability, their efforts are often fragmented and not integrated across all areas of operation. Sustainability evaluation in Pakistani HEIs is in its nascent stages, with no standardized framework aligned with the Sustainable Development Goals (SDGs). Through modification of the Sustainability Assessment Questionnaire (SAQ) and matching its dimensions—curriculum, operations, outreach, and governance with the relevant SDGs, this study aims to measure the sustainability performance of Pakistani higher education institutions (HEIs). By employing a mixed-methods design involving a literature review, expert opinions, and pilot survey, and making use of the Analytical Hierarchy Process (AHP) in assigning weights to key indicators and computing sustainability scores, the study aims to contribute to the assessment of the sustainability performance of Pakistani HEIs. Though curriculum and research fare moderately well, the evidence reflects significant gaps within outreach, student engagement, and administration. The findings highlight the need for comprehensive, SDG-congruent frameworks to support higher education institutions in systematically improving their sustainability policies. This research forms the foundation for future scholarly and policy discussions and contributes to the body of knowledge of institutional sustainability in developing countries.